ANALISIS PERSEPSI KARYAWAN TERHADAP KOMPENSASI DALAM MENINGKATKAN DISIPLIN KERJA PADA PT IONI JAYA TANGERANG - Iqlima Cahya Islami; Syawaludin Syawaludin (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Abstract. This study aims to analyze employees' perceptions of the compensation system in improving work discipline at PT Ioni Jaya Tangerang. This research employs a descriptive qualitative approach, with data collection techniques including in-depth interviews, observation, and documentation. The informants in this study consist of company management and employees from various departments, selected purposively based on their involvement and understanding of the compensation system and work discipline. The data analysis technique used in this study refers to the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The collected data were analyzed in depth to identify patterns, meanings, and the relationship between employees’ perceptions of compensation and their level of work discipline. The results of the study indicate that employees’ perceptions of the compensation system at PT Ioni Jaya vary. Some employees perceive that the compensation system is not fully fair and transparent, particularly in terms of salary, allowances, and incentives. This condition affects employees’ work motivation and has an impact on their level of discipline, such as lateness and inconsistent attendance. On the other hand, employees who have a positive perception of compensation tend to demonstrate better work discipline. This study concludes that the compensation system plays a significant role in shaping employees’ work discipline. Therefore, the company needs to improve its compensation system to be more fair, transparent, and structured in order to enhance employee motivation and work discipline in a sustainable manner. Keywords: Employee Perception, Compensation, Work Discipline, Qualitative Research